2007
DOI: 10.1152/ajpheart.01174.2006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atherosclerotic effects of sirolimus on human vascular smooth muscle cells

Abstract: Ma KL, Ruan XZ, Powis SH, Moorhead JF, Varghese Z. Antiatherosclerotic effects of sirolimus on human vascular smooth muscle cells. Am J Physiol Heart Circ Physiol 292: H2721-H2728, 2007. First published February 23, 2007 doi:10.1152/ajpheart.01174.2006.-Sirolimus is a potent immunosuppressive agent and has an anti-atherosclerotic effect through its anti-proliferative property. The present study was undertaken to investigate the effect of sirolimus on intracellular cholesterol homeostasis in human vascular smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 45 publications
(50 reference statements)
8
52
0
Order By: Relevance
“…[16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy. 24,25 In addition, there are differences in the rates of target vessel versus target lesion revascularization rates, implying that pathologic processes are modified in other regions of the stented coronary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy. 24,25 In addition, there are differences in the rates of target vessel versus target lesion revascularization rates, implying that pathologic processes are modified in other regions of the stented coronary.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Multiple studies have demonstrated the atherosclerotic attenuation of sirolimus in Apolipoprotein E-deficient mice and human vascular smooth muscle cells. [19][20][21][22] A variety of studies investigating coronary artery disease in heart transplant patients, who have baseline endothelial dysfunction, have shown that antiproliferatives such as sirolimus attenuate the rate of atherosclerotic progression. 29,30 In addition, paclitaxel is a well-known immunomodulatory agent and has also been associated with atherosclerotic regression in animal models, as well as reduced inflammation in stented porcine arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the cumulative percentage of RPM, as shown in Figure 6B, the RPM amount released per day gradually reduced, but there was always drug detected in the release solution, which can still play an inhibitory role in cell proliferation. 55 Drug can be released from the delivery system in a sustained manner to prolong exposure time and increase the drug-therapy efficacy. 56,57 Physically entrapped drugs were released mainly through the diffusion effect, so the driving force was reducing with the concentration of drugs in the core decreasing gradually.…”
Section: In Vitro Releasementioning
confidence: 99%
“…7 Second, everolimus has significant antimacrophage activity that is mediated by at least 2 potentially independent mechanisms, namely the inhibition of monocyte chemotaxis 8 and the induction of macrophage death by autophagy. 9,10 Third, everolimus prevents lipid accumulation in macrophages and SMCs due to inhibition of endogenous cholesterol synthesis, 11 downregulation of low-density lipoprotein (LDL) receptors and scavenger receptors, 12,13 as well as upregulation of cholesterol efflux genes. 12,13 Other beneficial effects include upregulation of endothelial nitric oxide synthase (eNOS) in low shear regions, which are susceptible to atherosclerosis, 14 and inhibition of hyaluronan deposition by SMCs, 15 a product that stimulates monocyte adhesion to the extracellular matrix.…”
mentioning
confidence: 99%